Integral clinical and neuroimaging criteria for the prognosis of spontaneous supratentorial intracerebral hemorrhage acute period outcome - A. A. Kuznietsov (Zaporožskij Medicinskij Žurnal)
The purpose of this study was to develop integrated clinical and neuroimaging criteria for the prediction of spontaneous supratentorial intracerebral hemorrhage (SSICH) acute period outcome.